Dampak Stres Dan Tekanan Kerja Terhadap Kinerja Karyawan Yang Dialami Oleh Karyawan Di Dalam Lingkungan Kerja Asuransi Pan Pacific - Michael A Usmany; Nurwulan Kusuma Dewi; Nova Rima (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Pan Pacific Insurance which operates in the fields of health insurance, home insurance, work insurance, car insurance provides a high service commitment to customers and stakeholders through innovative and solution products, of course this service will require employees to work very well in serving customers, so that It could be that it will put employees under great pressure at work. This research aims to determine the impact of work stress and pressure on employee performance experienced by employees in the Pan Pacific Insurance work environment. This research uses quantitative methods. The results of the research show (1) Based on the test results, it is known that Work Pressure (X1) has a calculated t value (1.884) > t table (0.157), or it can also be seen from the significance value of 0.00 < α = 0.05, from these calculations, it can be concluded that work pressure has a significant influence on employee performance experienced by employees in insurance and Pacific work environments, (2) Based on the results, it shows that the variable (X2) has a calculated t value of (0.555) > t table (0.157), or it can also be seen from the significance value of 0.002 < α= 0.05, from these calculations, it can be concluded that job satisfaction has a significant influence on employee performance experienced by employees in insurance and pacifist work environments; (3) The impact of stress experienced by employees in the insurance and Pacific work environment can have a significant effect on their well-being and performance. Excessive stress can lead to decreased productivity, increased absenteeism rates, and even potentially impact employees' mental and physical health.